2011
DOI: 10.1128/mcb.05393-11
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin-Like Protein 2 Binds Cardiolipin and Regulates Mitochondrial Biogenesis and Function

Abstract: Stomatin-like protein 2 (SLP-2) is a widely expressed mitochondrial inner membrane protein of unknown function. Here we show that human SLP-2 interacts with prohibitin-1 and -2 and binds to the mitochondrial membrane phospholipid cardiolipin. Upregulation of SLP-2 expression increases cardiolipin content and the formation of metabolically active mitochondrial membranes and induces mitochondrial biogenesis. In human T lymphocytes, these events correlate with increased complex I and II activities, increased intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
121
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 42 publications
8
121
1
Order By: Relevance
“…The function of these proteins has been linked to the regulation of assembly and function of multichain receptors (6,(10)(11)(12)(13). In line with this proposed function, we have recently shown that SLP-2 binds cardiolipin (CL) and promotes the formation of specialized CL-enriched microdomains that could facilitate the assembly of protein complexes within mitochondrial membranes (10).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The function of these proteins has been linked to the regulation of assembly and function of multichain receptors (6,(10)(11)(12)(13). In line with this proposed function, we have recently shown that SLP-2 binds cardiolipin (CL) and promotes the formation of specialized CL-enriched microdomains that could facilitate the assembly of protein complexes within mitochondrial membranes (10).…”
mentioning
confidence: 89%
“…As the amount of PHB1 in detergentsoluble fractions of control and SLP-2 T-K/O cells was similar, the loss of PHB1 from the insoluble fraction suggested an abnormal compartmentalization in the SLP-2 T-K/O mitochondrial membrane. We have recently shown that SLP-2 not only interacts with PHB but also binds CL, the signature phospholipid linked to detergentinsoluble microdomains of mitochondrial membranes (10). Therefore, the defect in mitochondrial membrane compartmentalization of PHB1 associated with SLP-2 deficiency prompted us to test if the content or distribution of CL was also impaired.…”
Section: Slp-2 Deficiency Is Associated With Abnormal CL Compartmentamentioning
confidence: 99%
See 1 more Smart Citation
“…Slp-2 coalesces with cardiolipin, and regulates the optimal assembly of prohibitins and other oxidative enzymes in the mitochondrial inner membrane. Slp-2 is located in the T-cell membrane receptor and modulates immunologic activity (4)(5)(6)(7). Mitochondrial dysfunction is an important pathogenic factor that aggravates oxidative damage in UC.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction is an important pathogenic factor that aggravates oxidative damage in UC. Deficiency of Phb-2 and Slp-2 may lead to mitochondrial dysfunction (2,4,5).…”
Section: Introductionmentioning
confidence: 99%